ANALISIS YURIDIS GUGATAN ANAK TERHADAP ORANG TUA - Rahayu, Titin Puji; Hidayah, Astika Nurul (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2024)
The cases filed by children against their parents in court reflect the mismatch between social practices and the applicable legal norms, especially in the context of Law No. 1/1974 regarding Marriage. In Islamic law, children have an absolute obligation to respect and be dedicated to their parents, as regulated in QS Al-Isra verses 23-24. However, in practice, lack of communication and changing social values often create conflicts between children and parents. This research uses normative legal method with statute approach and case approach to analyze legal protection for parents and the effectiveness of the mediation method in cases of children’s lawsuits against parents in court. The research specification uses descriptive analysis. The data collection method in this research uses the library research method. The results of the analysis show that in Indonesia there was no specific regulation that would protect parents, especially in legal cases where parents are sue by their children. This shows that there is a gap in the legal system that protects the position of parents when they are harmed by a lawsuit filed by a child. Therefore, clear regulations are needed to protect the rights of parents and ensure fairness and balance in these situations.